INFLUENCE OF INHIBITORY CONTROL ON PLANNING ABILITIES IN CHILDREN WITH MILD INTELLECTUAL DISABILITY - Gligorović, Milica; Buha, Nataša (Specijalna edukacija i rehabilitacija, 2016)
With regard to the fact that the tendency toward unsophisticated strategies is often related to difficulties with basic components of executive functions, the aim of this research was to determine the relation between planning abilities and inhibitory control in children with mild intellectual disability (MID). The sample included 56 children with idiopathic MID (IQ 50-70, mean=61.13, SD=7.14 years), of both genders (26/46.3% of girls), between 9.11 and 14.03 years of age (M=11.61; SD=1.29). Go no Go Task and Day/Night Stroop Task were used for the assessment of inhibitory control (delayed response to the agreed signal, conflict provoking motor responses, and inhibition of arrogant verbal responses), while Tower of London Test (ToL) was used for the assessment of planning abilities. Multivariate analysis of covariance (MANCOVA), paired samples t-test, Pearson’s correlation, and partial correlation coefficients were used in statistical analysis of the results. The results showed that the mistakes in Response delay set of Go-no-Go task were the only significant factor of primary Total move score variable (ToL). The influence of the ability to delay motor activity, assessed by Response delay set, on all ToL variables was statistically significant (p=0.003). The results lead to a conclusion that, during the processes of planning and executing activities, children with MID primarily rely on simple inhibitory mechanisms. Key words: mild intellectual disability, planning ability, inhibitory control